Randomized Controlled Trial to Compare the Safety and Efficacy of Tamsulosin, Solifenacin, and Combination of Both in Treatment of Double-J Stent-Related Lower Urinary Symptoms - Essam Shalaby; Abul-fotouh Ahmed; Aref Maarouf; Iman Yahia; Mohamed Ali; Ammar Ghobish (Advances in Urology)
Purpose. We evaluated the effectiveness and safety of tamsulosin, solifenacin, and combination of both in reducing double-J stent-related lower urinary symptoms. Materials and Methods. A total of 338 patients with double-J ureteral stenting were randomly divided, postoperatively, into 4 groups. In group I (), no treatment was given (control group), group II () received tamsulosin 0.4 mg daily, group III () received solifenacin 10 mg daily, and group IV () received a combination of both medications. Before insertion and 2 weeks after, all patients completed the International Prostate Symptom Score (IPSS), quality of life component of the IPSS (IPSS/Qol), Overactive Bladder Questionnaire (OAB-q), and Visual Analogue Pain Scale (VAPS) questionnaire. Results. The demographics and preoperative questionnaires scores of all groups were comparable. There were statistically significant differences in all scores in favour of groups II, III, and IV as compared to control group ( value < 0.005). Group IV showed statistically significant differences in total IPSS, QoL score, and OAB-q score as compared to groups II and III ( value < 0.001). Conclusions. Combined therapy of tamsulosin and solifenacin significantly alleviated lower urinary symptoms associated with double-J stents as compared to either medication alone.